Serious Complications of the Percutaneous A1 Pulley Release: Case Reports and Literature Review - Lee, Dong Chul; Lee, Kyung Jin; Lee, Hohyung; Koh, Sung Hoon; Kim, Jin Soo; Roh, Si Young (Archives of Plastic Surgery, 2024)
Percutaneous first annular pulley (A1 pulley) release, which has been increasingly used to treat trigger fingers, has been widely established as a safe and simple procedure. Multiple studies have reported positive results of percutaneous A1 pulley release. In this study, however, we report cases of patients who developed complications after undergoing percutaneous A1 pulley release at local clinics. A total of six patients visited our hospital for infectious complications after percutaneous A1 pulley release. Various sequelae such as damage to normal structures, insufficient procedure, and tissue necrosis were observed during the exploration. A retrospective study was conducted to identify the cause and trend of the observed complications by instruments (HAKI knife or needle). In the HAKI knife group, there was a tendency for damage to normal structures, while in the needle group, an insufficient release or serious soft tissue necrosis was observed. Based on these cases, our findings confirm the existence and characteristics of infectious complications following the percutaneous A1 pulley release. We further identify that the type of instrument used predicts the nature of complications. Thus, reliable and skilled performance of the procedure by experts is essential for safe treatment.
Keywords: trigger finger; percutaneous A1 pulley release; complications